A New Method for Structural Assessment of Topside Structure Subjected to Hydrocarbon Explosions. (2017) - Kim, Sang Jin; Kim, Bong Ju; Seo, Jung Kwan; Paik, Jeom Kee
Abstract: The primary aim of this study is to propose a new method for structural assessment of topside structures on offshore installations subjected to hydrocarbon explosions. In the present study, lots of dispersion and explosion scenarios are selected by probabilistic approach, and analyzed for definition of actual explosion loads. Then, sets of actual explosion loads from CFD simulation are transferred by interface program between CFD and FEA, and nonlinear structural consequence analyses is performed. The structural consequences under actual explosion loads investigated by FEA are used for a consequence exceedance curve which is a new method for structural assessment proposed in this study. The consequence exceedance curve can reduce uncertainties from simplification of load, structure and procedure. In addition, it can be directly found the structural behavior of topside structure under explosions at risk acceptance level by consequence exceedance curve.